2017
DOI: 10.18632/oncotarget.17115
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 2 inhibition synergises with bortezomib to target myeloma by enhancing endoplasmic reticulum stress

Abstract: The proteasome inhibitor bortezomib has proven to be invaluable in the treatment of myeloma. By exploiting the inherent high immunoglobulin protein production of malignant plasma cells, bortezomib induces endoplasmic reticulum (ER) stress and the unfolded protein response (UPR), resulting in myeloma cell death. In most cases, however, the disease remains incurable highlighting the need for new therapeutic targets. Sphingosine kinase 2 (SK2) has been proposed as one such therapeutic target for myeloma. Our obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…The molecular basis of UPR activation by SK2 inhibitors involves elevation of ceramide and changes in lipid composition of the ER membrane have been shown to directly activate IRE1α and PERK independently of lumenal unfolded proteins [5]. Importantly, WallingtonBeddoe et al [2] demonstrate that the findings in MM cell lines are recapitulated in vivo using the 5TGM1 C57BL/ KaLwRij murine model of myeloma.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The molecular basis of UPR activation by SK2 inhibitors involves elevation of ceramide and changes in lipid composition of the ER membrane have been shown to directly activate IRE1α and PERK independently of lumenal unfolded proteins [5]. Importantly, WallingtonBeddoe et al [2] demonstrate that the findings in MM cell lines are recapitulated in vivo using the 5TGM1 C57BL/ KaLwRij murine model of myeloma.…”
mentioning
confidence: 99%
“…Wallington-Beddoe et al [2] in this issue of Oncotarget have analysed a larger gene expression data set from CD138 + bone marrow plasma cells from newly diagnosed myeloma patients compared to normal healthy controls. The authors found that there was increased expression of several genes involved in sphingolipid biosynthesis, including serine palmitoyltransferase, 3-keto-dihydrosphingosine reductase, alkaline ceramidase and SK2.…”
mentioning
confidence: 99%
See 3 more Smart Citations